Relationship between oxygen radical absorbance capacity (ORAC) index, body composition and blood biochemical markers in overweight/obese compared to normal weight subjects: a cross-sectional study - Madani, Zahra; Moussavi Javardi, Maryam; Majdizadeh, Golnaz; Mostafaei, Zahra; Djazayeri, Seyyed Abolghassem; Karandish, Majid; Movahedi, Ariyo (Journal of health, population and nutrition, 2025)
Background Obesity is an important preventable disease, which promotes the development of chronic disorders by altering several factors including oxidative stress. Dietary antioxidants protect the body against oxidative stress. The purpose of this study was to evaluate the potential association of oxygen radical absorbance capacity (ORAC) index with obesity and its associated features in adults. Methods Participants were divided in two groups of normal weight and overweight/obesity. General characteristics were registered and a 147-item food frequency questionnaire was completed. Thereafter, anthropometric measurements were conducted. Biochemical indices were obtained from science and Research branch of Islamic Azad University of Tehran, Iran. The amount of the dietary ORAC index was estimated using the data provided by the USDA Foods Table. Results The results showed that there was a significant difference between the normal and overweight/obese groups in terms of body mass index (BMI) and waist-to-hip ratio (WHR) ( P = 0.0001). Participants with normal weight consumed more fruits and vegetables than another group. Also, the dietary ORAC index in normal individuals was higher than the case group, but there was not significant difference ( P = 0.352). There was also a significant inverse correlation between dietary ORAC and BMI and WHR, whereas a significant positive correlation between dietary ORAC and plasma HDL was observed ( P < 0.05). Conclusion Our findings suggest that dietary antioxidants is inversely associated with BMI, fasting blood glucose, triglyceride, total Cholesterol and LDL in both groups. It seems that following a diet rich in antioxidants can counteract obesity and its associated comorbidities.